Effects of Positive School Culture on Basic Education Quality: A Meta-Analysis - Ilun Muallifah; Junaedi Junaedi (Buletin Al-Turas, 2026)
Purpose The study was intended to synthesize empirical evidence on the effects of positive school culture on basic education quality, calculated pooled effect sizes, and identified key moderator variables. Method This meta-analysis made uses of PRISMA 2020 guidelines, a systematic search across Scopus, Web of Science, ERIC, and Google Scholar (2014–2024) to identify 75 peer-reviewed studies (N = 38,472; 24 countries). Effect sizes were computed as Hedges’ g under a random-effects model; moderators were examined via subgroup analysis and meta-regression. Results/findings Positive school culture produced large pooled effects on teacher performance (g = 0.68, 95% CI [0.59, 0.77]) and student engagement (g = 0.61, 95% CI [0.52, 0.70]). Emotional engagement was the most culturally responsive sub-dimension (g = 0.66). Both effects remained large after bias correction. Geographic region, school size, grade level, and publication year significantly moderated effect sizes. Conclusion Positive school culture was a robust predictor of teacher performance and student engagement in primary education, underscoring the centrality of school culture development in school improvement policies, especially in Indonesia and other Asian educational systems